2022
DOI: 10.3389/fpubh.2022.837724
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of College Student Hunger: What We Know and Where We Need to Go

Abstract: The first article on college food insecurity, published in 2009, sparked conversation on the dark secret many students face while seeking a college degree; they do not have secure access to food. Over 10 years later, numerous investigators around the globe have reported on the heightened prevalence of college food insecurity, the correlates that increase risk, and the detrimental outcomes associated with not having a secure source of food. In this manuscript, we describe the decade of research devoted to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 81 publications
1
38
0
Order By: Relevance
“…Sustainable approaches to creating a culture of food security and health equity are essential on college campuses. This type of approach requires moving beyond addressing basic needs (1)(2) . Instead, the aim would be to create a culture of food security on college campuses that supports students' nutritional needs, with a focus on health equity which provides "the personal agency and fair access to resources and opportunities needed to achieve the best possible physical, emotional, and social well-being" (3) .…”
Section: Position Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Sustainable approaches to creating a culture of food security and health equity are essential on college campuses. This type of approach requires moving beyond addressing basic needs (1)(2) . Instead, the aim would be to create a culture of food security on college campuses that supports students' nutritional needs, with a focus on health equity which provides "the personal agency and fair access to resources and opportunities needed to achieve the best possible physical, emotional, and social well-being" (3) .…”
Section: Position Statementmentioning
confidence: 99%
“…The overall impact of food insecurity among college students is still being studied, however, research to date has suggested that food insecurity during college impedes student health and academic success during college. For example, students who report being food insecure are more likely to have diminished academic achievement including lower GPA, behavioral problems, mental health concerns, and overall poorer self-rated general health (1,2,11,15,25) . Additionally, students report struggling with high levels of stress and disrupted sleep quality which have worsened during the COVID-19 pandemic (26) .…”
Section: Risk Factors and Impacts Of Food Insecuritymentioning
confidence: 99%
See 3 more Smart Citations